Margaretha Kramer-Hajos. Mycenaean Greece and the Aegean World: Palace and Province in the Late Bronze Age. - Rutter, Jeremy (Journal of Greek Archaeology, 2018)
Diachronic surveys of Mycenaean civilization, our term for the material culture that flourished above all on the central and southern Greek mainland during the six or seven centuries (ca. 1700/1600-1000 BC) we assign to the Late Bronze Age, typically and understandably focus on the regional cores of that culture in the northeast (Argolid and Corinthia) and southwest (Messenia) Peloponnese where it arose and has been most extensively documented. The overview of this culture provided by Margaretha Kramer-Hajos (hereafter MK-H) is refreshingly different in its spatial focus on the Euboean Gulf region of east-central Greece (figs. 1.1-1.2) as well as in its conceptual emphasis on certain aspects of network theory and human agency.